The politics of precaution: genetically modified crops in developing countries - Paarlberg, Robert L. (International Food Policy Research Institute, 2001)
Genetically modified (GM) food crops have inspired increasing controversy over the past decade. By the mid-1990s they were widely grown in the U.S., Canada, and Argentina, but precautionary regulations continue to limit their use elsewhere. The restrictive policies of Europe and Japan toward GM crops have been much discussed. Less attention has been paid to the policies affecting the adoption of GM crops in the developing world, where their potential impact on the availability and quality of food is even greater. In this book Robert L. Paarlberg looks at the policy choices regarding GM food made by four important developing countries: Kenya, Brazil, India, and China. Of these, so far only China has approved the planting of GM crops. Paarlberg identifies five policy areas in which governments of developing countries can either support or discourage GM crops: intellectual property rights, biosafety, trade, food safety, and public research and investment. He notes that highly cautious biosafety policies have so far been the key reason that Kenya, Brazil, and India have hesitated to plant GM crops. These cautious policies have been strongly reinforced by international market forces and international diplomatic and NGO pressures. China has been less cautious toward GM crops, in part because there is less opportunity in China for international organizations or independent critics of GM crops to challenge official policy.